2021
DOI: 10.19184/pk.v9i1.12228
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Hidroksipropil Metilselulosa dan Polivinil Pirolidon dalam Sediaan Mucoadhesive Buccal Film Diltiazem Hidroklorida

Abstract: Diltiazem HCl is a class of benzodiazepine calcium channel blockers used to treat angina pectoris, arrhythmias, and hypertension. Diltiazem HCl improves first-pass metabolism, a short half time of 3-5 hours, and bioavailability of diltiazem for oral administration of about 40%. Mucoadhesive buccal film diltiazem HCl releases the drug to the buccal mucosa, so the first pass metabolism can be avoided because of its absorption through the venous system that flows from the cheek. This study aimed to study HPMC pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…24 The results of this study were in accordance with previous research from Sari, et al spraying 0.5% sodium hypochlorite on alginate impression resulting in dimensional changes that were still within tolerance limits. 29 This study was also in accordance with the study of Amelia, et al which showed there was a change in dimensional stability which was still within the tolerance limits of alginate impression after 0.5% sodium hypochlorite was sprayed. 9 Disinfection of alginate impression with 10% castor oil in group C2 showed an effect on the dimensional stability of the study model.…”
Section: Discussionsupporting
confidence: 91%
“…24 The results of this study were in accordance with previous research from Sari, et al spraying 0.5% sodium hypochlorite on alginate impression resulting in dimensional changes that were still within tolerance limits. 29 This study was also in accordance with the study of Amelia, et al which showed there was a change in dimensional stability which was still within the tolerance limits of alginate impression after 0.5% sodium hypochlorite was sprayed. 9 Disinfection of alginate impression with 10% castor oil in group C2 showed an effect on the dimensional stability of the study model.…”
Section: Discussionsupporting
confidence: 91%
“…Film Nanoemulsion Apigenin (Buccal Film Ne-APG) Organoleptic tests were carried out including visual observations such as color, clarity, and odor of the wet mixture and buccal film the resulting 22 .…”
Section: Evaluation Characterization Of Buccalmentioning
confidence: 99%